Emerging contaminants as global environmental hazards. A bibliometric analysis (2019)
This paper presents a bibliometric analysis of peer-reviewed scientific literature on emerging contaminants published from 2000 through 2019. A total of 4968 documents (among research articles and review papers) collected from Scopus database were analyzed using the VOSviewer 1.6.11 software. According to our results, this topic has been capturing researchers’ attention over the years and the latter five years of the analysis timespan corresponds to the period of highest scientific productivity on this subject, when a 70.4% of all analyzed documents were published. United States, China, Spain, Italy and Canada were the tope5 most productive countries in terms of number of published works, while Science of the Total Environment, Chemosphere, Environmental Science and Pollution Research, Environmental Pollution and Water Research stood out as the journals with the highest number of publications, gathering a 31% of papers and 34% of all citations. According to the frequency of author keywords, the main specific research topic assessed by the researchers are the occurrence of pharmaceuticals and personal care products in wastewater and the removal of such pollutants by the application of adsorption and advanced oxidation processes.